Determination of Minimum Number of Frustule for Identification of Diatoms in Telaga Cebong, Dieng, Central Java, Indonesia - Oki Rachmalia Rozi; Tri Retnaningsih Soeprobowati; Riche Hariyati (Indonesian Society of Limnology, 2022)
Diatoms belong to the division of Bacillariophyta; their cell walls composition of silica (SiO2) was the primary characteristic of their structure. Diatoms are good for water quality assessment and paleolimnological analysis. The determination number of frustule which has to be counted for diatom is one of the critical steps in process identification. Several studies usually use a range starting from 100-600 frustules, which refers to the